Cerebrospinal Fluid Flow Parameters in Normal Subjects above 40 Years of Age - Rohilla, Seema; Kumar, Pradeep; Singh, Ishwar (Indian Journal of Radiology and Imaging, 2023)
Background Cerebrospinal fluid (CSF) flow is altered in many conditions like normal pressure hydrocephalus (NPH), aqueduct stenosis, or Chiari malformation. It is very important to know the normal CSF flow parameters for properly diagnosing these conditions. No data on CSF flow parameters of the Indian population are available. Hence, this study was undertaken to generate normative CSF flow parameters in the Indian population.Aim Our aim was to estimate normal CSF flow parameters across the cerebral aqueduct in Indian subjects over 40 years of age.Settings and Design This observational study was done in the tertiary care institute on subjects undergoing magnetic resonance imaging (MRI) for indications like headache and having normal MRI.Methods Phase-contrast quantitative flow sequence was done in 100 subjects perpendicular to the cerebral aqueduct on 3.0T MRI (Discovery 750w with GEM suit, GE, Milwaukee, WI, United States) using a dedicated 32-channel head coil with 10 cm/s velocity encoding. The region of interest was kept at the cerebral aqueduct in cross-section. The inbuilt software calculated flow-time and velocity-time graphs and calculated peak systolic velocity (PSV), peak diastolic velocity (PDV), systolic flow (SF), and diastolic flow (DF). Stroke volume (SV) was calculated by averaging systolic and DFs. p-Value < 0.05 was considered significant.Results Mean age was 53.72 ± 10.53 (40–78) years with 41 males and 59 females. PSV, PDV, SF, DF, and SV all showed a significant linear correlation with age with p-values of 0.001, 0.004, 0.009, <0.001, and <0.001, respectively. Only PDV (p = 0.035) and DF (p = 0.045) varied significantly with sex, values being higher in males.Conclusion All five CSF flow parameters studied vary positively with age, and this variation is linear. Normal decadal median values calculated for these parameters can act as baseline values for the local population and help in defining conditions like NPH.
Keywords: CSF flow; phase-contrast quantitative flow sequence; stroke volume